2019
DOI: 10.1177/1533033819851833
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a-5p Inhibits Cell Proliferation and Enhances Doxorubicin Sensitivity in HCC Cells via Targeting AURKA

Abstract: Objective: To investigate the role of miR-26a-5p in cell proliferation and doxorubicin sensitivity in hepatocellular carcinoma. Methods: We evaluated miR-26a-5p expression in hepatocellular carcinoma tissues and cell lines by reverse transcription polymerase chain reaction. Cell Counting Kit-8 was used to examine cell proliferation. Relationship between miR-26a-5p and aurora kinase A was evaluated by luciferase report system. Western blot was used to detect expression of aurora kinase A. Results: In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In the meantime, recent research discovers that, the abnormal regulation of miRNAs is recognized to be the key factor for the genesis and development of multiple diseases, including HCC. For instance, miR-26a down-regulates AURKA expression to suppress HCC ell proliferation and migration (17). Chang et al (18) veri ed that, miR-26a served as an independent marker for the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, recent research discovers that, the abnormal regulation of miRNAs is recognized to be the key factor for the genesis and development of multiple diseases, including HCC. For instance, miR-26a down-regulates AURKA expression to suppress HCC ell proliferation and migration (17). Chang et al (18) veri ed that, miR-26a served as an independent marker for the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Seven highly expressed miRNAs, which are mainly involved in cell proliferation, growth and apoptosis, were identified at the four developmental periods. Among these, miR-21-5p and miR-26a-5p have also been shown to be associated with the proliferation of melanoma and hepatocellular carcinoma cells, respectively [27,28]. As for the members of let-7, expressions of let-7i-5p, let-7f-5p and let-7g-5p have been revealed to regulate the regeneration rate of liver in mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that miR-26a-5p can also down-regulate MNAT1 to suppress malignant behaviours of OS cells. In addition, a few of recent studies reported that miR-26a-5p plays cancer-suppressive role in several other type of cancers, such as papillary thyroid carcinoma, colorectal cancer, breast cancer, hepatocellular carcinoma, and melanoma [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%